(untitled) (British Journal of Global Ecology and Sustainable Development, 2025)
This article explores the issue of enhancing motivation for foreign language learning among students of medical institutes within the framework of linguodidactics and foreign language teaching methodology. The study examines motivational factors influencing medical students’ engagement in foreign language acquisition and analyzes methodological challenges associated with teaching foreign languages in medical education. Particular emphasis is placed on the comparative application of teaching methods and the role of interactive, learner-centred approaches in increasing motivation. The findings highlight that well-structured instructional strategies and professionally oriented content significantly contribute to effective language learning outcomes among medical students.